A hybrid effectiveness-implementation cluster randomized trial of group CBT for anxiety in urban schools: rationale, design, and methods. (December 2015) - Eiraldi, Ricardo; Khanna, Muniya; Jawad, Abbas; Fishman, Jessica; Glick, Henry; Schwartz, Billie; Cacia, Jaclyn; Wandersman, Abraham; Beidas, Rinad
Abstract Background Schools present a context with great potential for the implementation of psychosocial evidence-based practices. Cognitive behavioral therapy (CBT) is an evidence-based practice that has been found to be very effective in treating anxiety in various community settings, including schools. Friends for Life (FRIENDS) is an efficacious group CBT protocol for anxiety. Unfortunately, evidence-based practices for anxiety are seldom employed in under-resourced urban schools, because many treatment protocols are not a good fit for the urban school context or the population, existing behavioral health staff do not receive adequate training or support to allow them to implement the treatment with fidelity, or school districts do not have the resources to contract with external consultants. In our prior work, we adapted FRIENDS to create a more culturally sensitive, focused, and feasible CBT protocol for anxiety disorders (CBT for Anxiety Treatment in Schools (CATS)). Methods/design The aim of this 5-year study is to evaluate both the effectiveness of CATS for urban public schools compared to the original FRIENDS as well as compare the implementation strategies (train-the-trainer vs. train-the-trainer + ongoing consultation) by conducting a three-arm, parallel group, type 2 hybrid effectiveness-implementation trial in 18 K-8 urban public schools. We will also assess the cost-effectiveness and the mediators and moderators of fidelity. Ninety therapists, 18 agency supervisors, and 360 children will participate. The interactive systems framework for dissemination and implementation guides the training and support procedures for therapists and supervisors. Discussion This study has the potential to demonstrate that agency therapists and supervisors who have had little to no prior exposure to evidence-based practices (EBPs) can implement an anxiety disorder EBP with fidelity. Comparisons of the implementation strategies would provide large urban mental health systems with data to make decisions about the adoption of EBPs. Trial registration ClinicalTrials.gov, NCT02651402